Robert B. Parker's Bye bye baby [large type] - Parker, Robert B., 1932-2010; Atkins, Ace (Thorndike Press large print core series., 2022)
"Carolina Garcia-Ramirez is taking on the establishment with her progressive agenda. When her chief of staff reaches out to Spenser for security and help finding the culprits of what he believes to be the most credible threats, Garcia-Ramirez is less than thrilled. She's used to the antipathy and intimidation women of color often face when seeking power. To her, it's all noise. But it doesn't take long for Spenser to cross paths with an extremist group called The Minutemen. This is Spenser doing what he does best, living by a personal code and moral compass that can't ever be broken"--